2009
DOI: 10.1123/ijspp.4.4.461
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Strength Characteristics and Unweighted and Weighted Vertical Jump Height

Abstract: Purpose:To investigate the relationship between maximum strength and differences in jump height during weighted and unweighted (body weight) static (SJ) and countermovement jumps (CMJ).Methods:Sixty-three collegiate athletes (mean ± SD; age= 19.9 ± 1.3 y; body mass = 72.9 ± 19.6 kg; height = 172.8 ± 7.7 cm) performed two trials of the SJ and CMJ with 0 kg and 20 kg on a force plate; and two trials of mid-thigh isometric clean pulls in a custom rack over a force plate (1000-Hz sampling). Jump height (JH) was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
179
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(200 citation statements)
references
References 24 publications
14
179
2
5
Order By: Relevance
“…In SJ, since they start from a static position, the athletes need to apply greater force to accelerate the body in order to perform the movement 21 . In this respect, improvement of these scores indicates an increase in force production capacity, as demonstrated in studies that correlated maximum isometric and dynamic force with SJ performance 22,23 and observed that athletes with greater force levels exhibited better SJ performance. According to Faude et al 12 , after high-intensity actions, particularly straight sprints and vertical jumps that occur during crucial moments of a soccer game, it is essential that athletes train and develop these skills.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In SJ, since they start from a static position, the athletes need to apply greater force to accelerate the body in order to perform the movement 21 . In this respect, improvement of these scores indicates an increase in force production capacity, as demonstrated in studies that correlated maximum isometric and dynamic force with SJ performance 22,23 and observed that athletes with greater force levels exhibited better SJ performance. According to Faude et al 12 , after high-intensity actions, particularly straight sprints and vertical jumps that occur during crucial moments of a soccer game, it is essential that athletes train and develop these skills.…”
Section: Discussionmentioning
confidence: 85%
“…Key words: Athlete; Intervention; Sport performance. (CMJ: F= 26,23, p<0,01; %mudança= 11,3; SJ: F= 23,16, p<0,01, %mudança= 9,8 …”
mentioning
confidence: 99%
“…Athletes performed two SJs and two CMJs for unloaded (0 kg) and loaded conditions (20 kg) for a total of four jumps. Similarly to the procedure by Kraska et al (2009), the weight of the PVC pipe was considered negligible and served as the 0 kg condition, while 20 kg bar served as the loaded condition (See Figure 1 below). The loaded conditions were included in order to simulate a situation of fatigue and to examine how subjects respond to an external load in jumping performance.…”
Section: Instrumentation and Data Collection Proceduresmentioning
confidence: 99%
“…The apparatus and standard positioning were established based on previously published data from Haff et 16 and Kraska et al 14 Bar heights were set specific to the individual, corresponding to a knee angle of 125˚ ± 5˚ and a hip angle of 175˚ ± 5˚ (see Figures 2 and 3). Athletes' hands were fixed to the bar using weightlifting straps and athletic tape to prevent their hand movement and to ensure a maximum effort could be given without the limitation of hand grip strength.…”
Section: Instrumentation and Data Collection Proceduresmentioning
confidence: 99%
“…Time interval measured at 50% of maximal force presents the time for S gradient, i.e. starting/initial acceleration implementation/ ralization, while at the level of 180 ms it presents the most characteristic duration of contact with the ground during running in submaximal regime of exertion, abrupt changes in direction and vertical jumps (Čoh, 2010;Čoh & Bošnjak, 2010;Gruber & Gollhofer, 2004;Haff et al, 2005;Hakkinen, 1991;Ikemoto et al, 2007;Kraska et al, 2009;Zatsiorsky & Kraemer, 2006). These time intervals are typical for sports with complex demonstration of motoric properties, so it is not strange that these indicators of explosiveness in the mentioned time intervals were abstracted as the last, IV factor.…”
Section: Figurementioning
confidence: 99%